Interfacial Super‐Assembly of Ordered Mesoporous Carbon‐Silica/AAO Hybrid Membrane with Enhanced Permselectivity for Temperature‐ and pH‐Sensitive Smart Ion Transport. (8th November 2021) - Zhou, Shan; Xie, Lei; Li, Xiaofeng; Huang, Yanan; Zhang, Liping; Liang, Qirui; Yan, Miao; Zeng, Jie; Qiu, Beilei; Liu, Tianyi; Tang, Jinyao; Wen, Liping; et al.
Abstract: Nanofluidic devices have been widely used for diode‐like ion transport and salinity gradients energy conversion. Emerging reverse electrodialysis (RED) nanofluidic systems based on nanochannel membrane display great superiority in salinity gradient energy harvesting. However, the imbalance between permeability and selectivity limits their practical application. Here, a new mesoporous carbon‐silica/anodized aluminum (MCS/AAO) nanofluidic device with enhanced permselectivity for temperature‐ and pH‐regulated energy generation was obtained by interfacial super‐assembly method. A maximum power density of 5.04 W m −2 is achieved, and a higher performance can be obtained by regulating temperature and pH. Theoretical calculations are further implemented to reveal the mechanism for ion rectification, ion selectivity and energy conversion. Results show that the MCS/AAO hybrid membrane has great superiority in diode‐like ion transport, temperature‐ and pH‐regulated salinity gradient energy conversion. Abstract : The synthesis of a mesoporous carbon‐silica/anode alumina oxide (MCS/AAO) hybrid membrane by interfacial super‐assembly is reported. The MCS/AAO hybrid membrane with enhanced permselectivity exhibits diode‐like ion transport behavior and superior temperature‐ and pH‐sensitive salinity gradient energy conversion performance.